Patient explicit consideration of tradeoffs in decision making about rectal cancer treatment: benefits for decision process and quality of life. (3rd July 2019) - Pieterse, Arwen H.; Kunneman, Marleen; van den Hout, Wilbert B.; Baas-Thijssen, Monique; Geijsen, Elisabeth D.; Ceha, Heleen M.; Muller, Karin M.; van der Linden, Yvette M.; Marijnen, Corrie A. M.; Stiggelbout, Anne M.
Abstract: Introduction: Patient preferences are often not discussed in treatment decisions in oncology. We introduced an online values clarification method (VCM) to help newly diagnosed rectal cancer patients participate in shared decision making about short-course preoperative radiotherapy. Material and Methods: We offered a link to the VCM to a subset of consecutive patients before the pretreatment consultation with the radiation oncologist. Consultations were audiotaped and coded for expressions of patient preferences. Patients were asked to complete pre- and post-consultation questionnaires. Questionnaires assessed values clarity, decision regret and presence and impact of fecal incontinence and sexual problems. Results: Of 135 patients who had their consultation audiotaped and completed questionnaires, 35 received and accessed the VCM-link. Patients in the VCM-group slightly more often expressed preferences during consultations. Questionnaire data showed that patients in the VCM-group did not differ in how clear their values were, but experienced lower regret and less impact of treatment harms at 6 months follow-up; differences were non-significant but in the same direction at 12 months. Discussion: This is the first study to assess the effect of an adaptive conjoint analysis-based VCM on actual patient-clinician communication, and long-term decision regret and impact of treatment harms. Being explicitly invited to think about treatment benefits and harms seems to help patients to live with treatment consequences.